Analisis Faktor Kesulitan Guru SD Dalam Penerapkan Model Pembelajaran Inovatif Berbasis Konstruktivisme Pada Proses Belajar Mengajar di SD Negeri Kota Malang - Yulita Pujiharti; Loesita Sari (IKIP Budi Utomo Malang, 2018)
The ultimate goal of all government programs in education , including certifcation program is to improve the quality of education , resulting in Indonesian human resources are superior . Surprising fndings of several previous studies , that almost most teachers teach to the learning patterns of the old classical learning models. Therefore the aim of this study was to analyze factors Elementary School Teacher Diffculties In Implementing Innovative Learning Model Based On Constructivist Teaching and Learning in Elementary School Malang . The method used is to use mapping and analyzing several factors that could be expected to inﬂuence the pattern of applied learning classroom teachers . The study population is a public elementary school teacher Malang number 196 school.Tehnik scattered cluster area sampling is random sampling with a sample of 125 teacher .Analisis by mapping the data , look for the percentage of each district and for the use of multiple regression analyzes durbin Watson method .Results of Analysis states that 1 ) Map pattern of teaching is the most innovative teachers in District Blimbing 2 ) Teacher Elementary School in Malang assume that the level of diffculty of planning and implementation of innovative teaching model at the level sedang.3 ) Variables that affect the pattern of Innovative Learning constructivism is based on variable diffculty in the preparation of lesson plans and teachers’ confdence in the ability of students to do the teaching and learning process based Innovative constructivism , while 18 others are considered predictors of no effect